Implementation of Consumer Protection for Return Rights Replaced by Candy by Abel Supermarket in Telang - Cahyatri Lisdanna Sari; Arina Saidah Putri; Sabrina Anastasya Aurelia; Lydia Fanggi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the practice of replacing change with candy or donations that occurs at Toko Abel, and its implications for the protection of consumer rights based on the Consumer Protection Law (UUPK). According to UUPK, consumers have the right to receive change according to the amount that has been paid, and replacing money with other goods that are not comparable violates the basic rights of consumers. This practice also contradicts the provisions of Law Number 7 of 2011 concerning Currency, which states that only paper and metal money are valid for use as a means of payment in Indonesia. Through interviews with consumers and business actors, this study shows that although replacing change with candy is often considered a minor problem, this practice has the potential to reduce consumer trust and damage long-term relationships between consumers and business actors. The results of this study suggest that business actors comply with applicable legal provisions, ensure that consumer rights are fulfilled, and seek legitimate and fair solutions in dealing with the problem of a shortage of coins at the cashier. Thus, this study emphasizes the importance of consumer protection in every transaction to maintain fairness and transparency in trade relations.